iF yearbook product. - International Forum Design (Basel : Birkhäuser)
The iF product design award covers all areas of product design. It serves as a platform for design-relevant innovations, thus recognizing today's globally networked world and its related dynamics. Since 1953, the iF product design award has been recognized as a label for good design.
Keywords: Ontwerpen